Influence of maturation level on the development of physical performance in young combat sports athletes: a scoping review - Athayde, M. S. da S.; Kons, R. L.; Dopico-Calvo, X.; de Góes, G. H.; Detanico, D. (Sport Sciences for Health, 2024)
Background Combat sports practices during childhood and adolescence are accompanied by several beneficial effects. During this phase, the maturity status and timing play an important role for the young athletes and must be considered in youth training programs, especially for those who are about to start (or have already started) formal training and competitions.